Contested ideas and possible futures for the university. Issue 1 (19th December 2019) - Conway, Maree
Abstract : Purpose: This study aims to identify and explore the nature of ideas of the university in the present to demonstrate how the ideas both enable and constrain the emergence of its possible futures. Design/methodology/approach: An integrated literature review of work on the western university was undertaken to identify the defining elements of ideas discussed in the literature – purpose, social legitimacy and embedded future – for the university in each idea. Findings: Four contested and co-existing ideas of the university in the present were identified, and the nature of their co-existence and their underpinning assumptions about the purpose and social legitimacy and the embedded future held by each idea are made explicit. Research limitations/implications: The paper focuses only on public, non-profit western universities as they exist in Australia, Europe, the UK, Canada and the USA in the present. Whether other forms of the university such as private non-profit and private for-profit "fit" into the four ideas and university types identified here was not explored and is a topic for future research. Originality/value: The paper draws on an extensive literature to identify a new frame to understand the evolution of multiple ideas of the university, the impact of these ideas on the empirical organisational form of the university and how they shape assumptions about the university's possible futures.